Food security reduces multiple HIV infection risks for high‐vulnerability adolescent mothers and non‐mothers in South Africa: a cross‐sectional study. Issue 8 (25th August 2022) - Cluver, Lucie; Rudgard, William E.; Toska, Elona; Orkin, Mark; Ibrahim, Mona; Langwenya, Nontokozo; Kuo, Caroline; Xaba, Nonhlanhla; Roehm, Kai; Smith, Michael; Bernardini, Sara; Giordana, Giovanni; et al.
Abstract: Introduction: Adolescent girls and young women, including adolescent mothers, in Southern Africa have high HIV seroconversion and transmission. We need to know which risks drive HIV infections, and what can reduce these risks. Methods: We interviewed 1712 adolescent girls and young women (11–23 years), including 1024 adolescent mothers who had conceived before age 20 and had a living child, from two health municipalities of South Africa's Eastern Cape Province between March 2018 and July 2019. Recruitment was through multiple community, school and health facility channels. Associations between adolescent motherhood and seven HIV risk behaviours (multiple sexual partners, transactional sex, age‐disparate sex, condomless sex, sex on substances, alcohol use and not in education or employment) were investigated using the generalized estimating equations method for multiple outcomes specified with a logit link and adjusting for nine covariates. Using the same model, we investigated associations between having enough food at home every day in the past week (food security) and the same seven HIV risk behaviours. When we found evidence of moderation by HIV status, we report stratum‐specific odds ratios. Results: Mean age was 17.51 years (SD: 2.54), 46% participants were living with HIV. Compared to non‐mothers, adolescent mothers had lower odds of alcohol use (AOR = 0.47, 95% CI = 0.29–0.75), but higher odds of multiple sexual partners (AOR = 1.93, 95% CI = 1.35–2.74), age‐disparate sex (HIV‐uninfected AOR = 1.73, 95% CI = 1.03–2.91; living with HIV AOR = 5.10, 95% CI = 2.98–8.73), condomless sex (AOR = 8.20, 95% CI = 6.03–11.13), sex on substances (AOR = 1.88, 95% CI = 1.10–3.21) and not in education/employment (HIV‐uninfected AOR = 1.83, 95% CI = 1.19–2.83; living with HIV AOR = 6.30, 95% CI = 4.09–9.69). Among non‐mothers, food security was associated with lower odds of multiple sexual partners (AOR = 0.45, 95% CI = 0.26–0.78), transactional sex (AOR = 0.32, 95% CI = 0.13–0.82) and not in education/employment (AOR = 0.48, 95% CI = 0.29–0.77). Among adolescent mothers, food security was associated with lower odds of transactional sex (AOR = 0.17, 95% CI = 0.10–0.28), age‐disparate sex (AOR = 0.66, 95% CI = 0.47–0.92), sex on substances (AOR = 0.51, 95% CI = 0.32–0.82), alcohol use (AOR = 0.45, 95% CI = 0.25–0.79) and not in education/employment (AOR = 0.56, 95% CI = 0.40–0.78). Conclusions: Adolescent motherhood is associated with multiple vulnerabilities to HIV infection and transmission. Social protection measures that increase food security are likely to reduce HIV risk pathways for adolescent girls and young women, especially adolescent mothers.